Women in American operas of the 1950s : undoing gendered archetypes - Hershberger, Monica A. (Eastman studies in music ;, 2023)
"In the 1950s, composers and librettists in the United States were busy seeking to create an opera repertory that would be deeply responsive to American culture and American concerns. They did not break free, however, of the age-old paradigm so typically expressed in European opera: that is, of women as either saintly and pure or sexually corrupt, with no middle ground. As a result, in American opera of the 1950s, women risked becoming once again opera's inevitable victims. Yet the sopranos who were tasked with portraying these paragons of virtue and their opposites did not always take them as their composers and librettists made them. Sometimes they rewrote, through their performances, the roles they had been assigned. Sometimes they used their lived experiences to invest greater authenticity in the roles. With chapters on The Tender Land, Susannah, The Ballad of Baby Doe, and Lizzie Borden, this book analyzes some of the most performed yet understudied works in the American-opera canon. It acknowledges Catherine Clément's famous description of opera as "the undoing of women," while at the same time illuminating how singers like Beverly Sills and Phyllis Curtin worked to resist such undoing, years before the official resurgence of the American feminist movement. In short, they ended up helping to dismantle powerful gendered stereotypes that had often reigned unquestioned in opera houses until then"--